2022
DOI: 10.1007/s40519-021-01353-8
|View full text |Cite
|
Sign up to set email alerts
|

Orthorexia nervosa and dieting in a non-clinical sample: a prospective study

Abstract: Purpose Orthorexia Nervosa (ON) is characterised by excessive attention to a dietary regimen perceived as healthy. A critical factor in the distinction between ON and other eating disorders (EDs) is the dichotomy of quality-versus-quantity of food intake. We investigated whether specific types of diet or dieting frequency are associated with orthorexic features, explored the overlap between ON and EDs symptoms, and examined which constructs are predictive of ON after 6 months. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 72 publications
1
10
0
3
Order By: Relevance
“…42 Grindr usage has been found to negatively in uence user body image and satisfaction through its impact on personal feelings of sexual objecti cation, weight stigma, and social comparisons. 43 In this current study, Polish men were found both have higher risk of ON-related behaviours, and to use Grindr more often than Spanish men. Part of this relationship may be in uenced by increases stressors related to hypersexualized masculinity and the need to present a speci c body type to increase likelihood of sexual connection when suing Grindr.…”
Section: Discussionsupporting
confidence: 44%
“…42 Grindr usage has been found to negatively in uence user body image and satisfaction through its impact on personal feelings of sexual objecti cation, weight stigma, and social comparisons. 43 In this current study, Polish men were found both have higher risk of ON-related behaviours, and to use Grindr more often than Spanish men. Part of this relationship may be in uenced by increases stressors related to hypersexualized masculinity and the need to present a speci c body type to increase likelihood of sexual connection when suing Grindr.…”
Section: Discussionsupporting
confidence: 44%
“…Moreover, our study confirmed the importance of dieting as an ON risk factor. Previous studies suggested a relationship between ON and specific, restrictive nutritional approaches, from simply being on a diet to adhering to vegetarianism and other specific dietary approaches [ 9 , 13 , 14 , 15 , 37 , 38 , 39 ]. Although in this study we did not find any relationship with specific diet regimes, probably because of the reduced number of participants who specified the type of diet followed, data showed that the diet played an essential role.…”
Section: Discussionmentioning
confidence: 99%
“…Grindr usage was also found to negatively influence user body image and satisfaction through its impact on personal feelings of sexual objectification, weight stigma, and social comparisons [36]. In this current study, Polish men were found both have higher risk of ON-related behaviours, and to use Grindr more often than Spanish men.…”
Section: Discussionmentioning
confidence: 43%